DEVELOPMENT OF INTERACTIVE MULTIMEDIA FOR CLEAN AIR FOR BREATHING IN THE CONTEXT OF CLIMATE CHANGE FOR ELEMENTARY SCHOOLS - Karhada Karhada; Hartono; Adeng Slamet; Makmum Raharjo (Universitas Majalengka, 2024)
In the digital era, conventional learning methods in schools are not effective enough to convey important concepts, so more interactive and interesting learning media are needed in accordance with the nature and times of students, so this research aims to produce interactive multimedia products that are valid, practical and effective using applications. Canva and Power Point to improve students' understanding and learning outcomes. The subjects of this research were fifth grade students at SD Negeri 10 Palembang. The development model used is Hannafind and Peck. Data collection techniques include walkthroughs, interviews, questionnaires and tests. From the research results, validity tests were carried out by design, material and language experts whose results were declared very valid with an average of 93%. For the practicality test carried out by students, the results were stated to be very practical with an average of 83%. For the effectiveness test, it can be seen from student learning outcomes which increased from a pretest average of 60.65 to a posttest of 91.74. So it can be concluded that Interactive Multimedia on the Importance of Clean Air for Breathing in the Context of Climate Change in Class V Elementary School is declared valid, practical and effective on student learning outcomes.